Pengaruh Model Discovery Learning Terhadap Kemampuan Berpikir Kritis Matematis Siswa Kelas VIII MTs NW Pringgabaya Tahun Ajaran 2024/2025 - Siti Khaerunnisa; Azmi, Syahrul; Kurniawan, Eka (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aimed to determine the impact of implementing the discovery learning model on the critical thinking skills in class VIII at MTs NW Pringgabaya during the 2024/2025 school year. This research is a type of quasi-experiment. The study population consisted of VIII grade students at MTs NW Pringgabaya, divided into three classes. Cluster random sampling was used to select the sample, after conducting a homogeneity test on each population class. The experimental class, which applied the discovery learning model, was class VIII A, and the control class, which applied the direct learning model, was class VIII B. Data were collected using a critical thinking test and analyzed using an independent samples t-test. The results of the analysis showed that the , and the results of the calculation of effect size using Cohen's formula amounted to 0.51, therefore, it can be concluded that the application of the discovery learning model has an effect on the critical thinking skills of Class VIII students at MTs NW Pringgabaya.